THE ROLE OF DATA JOURNALISM IN CENTRAL ASIAN MEDIA СOUNTRIES - Jienbaeva Aygul Abdramanovna (European Science Publishing, 2024)
Data journalism is a new field that has been developing in Central Asian media countries for the past few years.This article stresses the role and use of data journalism in the media of Central Asia countries. Also, the best data materials published in the media of each country are analyzed.
Keywords: Data, infographics, fact, statistics, diagram, illustration.